Implantable collamer lens and femtosecond laser for myopia: comparison using an adaptive optics visual simulator - Pérez-Vives,Cari (2014)
Purpose: To compare optical and visual quality of implantable collamer lens (ICL) implantation and femtosecond laser in situ keratomileusis (F-LASIK) for myopia. Methods: The CRX1 adaptive optics visual simulator (Imagine Eyes, Orsay, France) was used to simulate the wavefront aberration pattern after the two surgical procedures for -3-diopter (D) and -6-D myopia. Visual acuity at different contrasts and contrast sensitivities at 10, 20, and 25 cycles/degree (cpd) were measured for 3-mm and 5-mm pupils. The modulation transfer function (MTF) and point spread function (PSF) were calculated for 5-mm pupils. Results: F-LASIK MTF was worse than ICL MTF, which was close to diffraction-limited MTF. ICL cases showed less spread out of PSF than F-LASIK cases. ICL cases showed better visual acuity values than F-LASIK cases for all pupils, contrasts, and myopic treatments (p<0.05). No statistically significant differences were found in contrast sensitivities between ICL and F-LASIK cases with -3-D myopia for both pupils for all evaluated spatial frequencies (p>0.05). For -6-D myopia, however, statistically significant differences in contrast sensitivities were found for both pupils for all evaluated spatial frequencies (p<0.05). Contrast sensitivities were better after ICL implantation than after F-LASIK. Conclusions: ICL implantation and F-LASIK provide good optical and visual quality, although the former provides better outcomes of MTF, PSF, visual acuity, and contrast sensitivity, especially for cases with large refractive errors and pupil sizes. These outcomes are related to the F-LASIK producing larger high-order aberrations.